The External Effect of Urban Schooling Attainment on Workers’ Incomes in Ecuador (2014)
We estimate the direct and external effects of levels of schooling on personal income in Ecuador in 2011, using data for 69,653 individuals in 567 municipalities. Using a Mincerian model that includes municipal levels of schooling and the size of the municipality and controls for endogeneity, we find that each year of individual schooling raises individual income by 8.5 percent and each year of municipal schooling raises individual income by 2.2 percent. The external effect of an additional year of schooling is larger for workers with more schooling, for those with higher incomes, and for those in more educated municipalities.